Painless Photodynamic Therapy Triggers Innate and Adaptive Immune Responses in a Murine Model of UV‐induced Squamous Skin Pre‐cancer. (22nd November 2020) - Anand, Sanjay; Govande, Mukul; Yasinchak, Anton; Heusinkveld, Lauren; Shakya, Sajina; Fairchild, Robert L.; Maytin, Edward V.
Abstract: Painless photodynamic therapy (p‐PDT), which involves application of photosensitizer and immediate exposure to light to treat actinic keratosis (AK) in patients, causes negligible pain on the day of treatment but leads to delayed inflammation and effective lesion clearance (Kaw et al ., J Am Acad Dermatol 2020). To better understand how p‐PDT works, hairless mice with UV‐induced AK were treated with p‐PDT and monitored for 2 weeks. Lesion clearance after p‐PDT was similar to clearance after conventional PDT (c‐PDT). However, lesion biopsies showed minimal cell death and less production of reactive oxygen species (ROS) in p‐PDT treated than in c‐PDT‐treated lesions. Interestingly, p‐PDT triggered vigorous recruitment of immune cells associated with innate immunity. Neutrophils (Ly6G+) and macrophages (F4/80+) appeared at 4 h and peaked at 24 h after p‐PDT. Damage‐associated molecular patterns (DAMPs), including calreticulin, HMGB1, and HSP70, were expressed at maximum levels around 24 h post‐p‐PDT. Total T cells (CD3+) were increased at 24 h, whereas large increases in cytotoxic (CD8+) and regulatory (Foxp3+) T cells were observed at 1 and 2 weeks post‐p‐PDT. In summary, the ability of p‐PDT to eliminate AK lesions, despite very little overt cellular damage, appears to involve stimulation of a local immune response. Abstract : Painless photodynamic therapy (p‐PDT), involving application of photosensitizer and immediate light exposure, causes negligible pain but results in effective therapy. In a murine skin pre‐cancer model, lesion clearance after p‐PDT was similar to clearance after conventional PDT (c‐PDT). However, cell death and production of ROS were compromised in p‐PDT‐treated lesions. Interestingly, p‐PDT triggered vigorous recruitment of immune cells associated with innate (neutrophils and macrophages) and adaptive (CD3+, CD8+ and Foxp3+ T cells) immunity. Expression of Damage Associated Molecular Patterns (DAMPs) were also observed. In summary, p‐PDT, despite very little cellular damage, appears to involve stimulation of a local immune response.